Perturbative odderon in quasidiffractive photon-photon scattering - Braunewell, Stefan; Ewerz, Carlo (Physical review. D, Particles, fields, gravitation, and cosmology, 2004)
We study the perturbative Odderon in the quasidiffractive process γ(*)γ(*)→ηcηc. At high energies this process is dominated by Odderon exchange and can be viewed as the theoretically cleanest test of the perturbative Odderon. We calculate the differential and total cross section, as well as the dependence on the energy and on the photon virtualities, taking into account the effects of resummation of logarithms of the energy. The results are compared with those obtained with a simple exchange of three noninteracting gluons. We present the expected cross section for this process at a future Linear Collider and discuss implications for other processes involving the perturbative Odderon.
Gesehen am 23.11.2017